FAKTOR FAKTOR YANG MEMPENGARUHI IBU HAMIL TERHADAP PEMANFAATAN PROGRAM TRIPLE ELIMINASI DAN PMTCT - Karo, Marni BR; Rahayu, Dewi Dedeh; Telaumbanua, Linda K (Siklus : Journal Research Midwifery Politeknik Tegal, 2023)
HIV is a global health problem, including Indonesia, and a threat to the health and safety of mothers and children it carries because more than 90% of the cases of HIV - infected babies are caused by vertical infections. By 2020 the HIV positive maternal population reached 6,094 out of 2,404,754 expectant mothers examined. So the first step governments can do to reduce infections by screening HIV over triple elimination and PMTCT programs. This study uses quantitative research designs, with detailed cross-sectional research designs and large sample studies were 76 pregnant mothers. Studies show that the factor found in connection with the benefit of the program triple elimination and PMTCT by expectant mothers is education (p-value 0.027), knowledge (p-value), health facilities (p-value 0.042), factor boosters. Whereas the factor that has not been found in connection with the use of the triple elimination and PMTCT programs by pregnant mothers is age (p-value 0.838), work (p-value 1,000), experience (p-value 0.770), time availability (p-value 0.862). They can conclude that there are 4 factors influencing pregnant mothers to the use of the triple elimination and PMTCT programs in the karese-city medical centers of education, knowledge, health facilities and driving factors from those closest to them. The other four factors that make no difference to the utilization of the program triple elimination and PMTCT are age, job, experience and time availability.